Comprehensive comparison of different parts of Paeonia ostii, a food-medicine plant, based on untargeted metabolomics, quantitative analysis, and bioactivity analysis - Zheng, Yaping; Li, Pei; Shen, Jie; Yang, Kailin; Wu, Xinyan; Wang, Yue; Yuan, Yu-he; Xiao, Peigen; He, Chunnian (Frontiers in Plant Science, 2023)
Paeonia ostii T.Hong & J.X.Zhang (s.s.) (Chinese name, Fengdan), a widely cultivated food-medicine plant in China, which root barkes, seed kernels and flowers are utilized for their medicinal and edible values, respectively. However, other parts of the plant are not used efficiently, in part due to a poor understanding of their chemical composition and potential biological activity. Untargeted UPLC-Q-TOF-MS metabolomics were applied to characterize the metabolic profiles of ten different parts of P. ostii. A total of 160 metabolites were alternative identified definitely or tentatively, which were significant different in various plant parts by multivariate statistical analysis. Quantitative analysis showed that underutilized plant parts also contain many active ingredients. Compared with the medicinal part root bark, the root core part still contains a higher content of paeoniflorin (17.60 ± 0.06 mg/g) and PGG (15.50 ± 2.00 mg/g). Petals, as an edible part, contain high levels of quercitrin, and stamens havehigher methyl gallate and PGG. Unexpectedly, the ovary has the highest content of methyl gallate, and rather high levels of PGG (38.14 ± 1.27 mg/g), and it also contains surprisingly high concentrations of floralalbiflorin I. Paeoniflorin (38.68±0.76 mg/g) have the most abundant in leaves, the content even higher than in the root bark respectively. And branches are also rich in a variety of catechin derivatives and active ingredients such as hydrolysable tannins. Seed kernels also contains fairly high levels of paeoniflorin and albiflorin. Fruit shells still contain a variety of components, although not at high levels.Seed coats, as by-products removed from peony seeds before oil extraction, have high contents of stilbenes, such as trans-gnetin H and suffruticosol B, showing the significant potential for exploitation.Except for the seed kernels, extracts obtained from other parts exhibited good antioxidant activity in DPPH, ABTS, and FRAP assays (0.09-1.52 mmolTE/g). Five compounds (gallic acid, PGG, transresveratrol, kaempferol, and quercitrin) were important ingredients that contributed to their antioxidant activities. Furthermore, P. ostii seed cakes were first reported to possess agonistic activity towards CB1/CB2 receptors. This study provides a scientific basis for the further development and utilization of